2007
DOI: 10.1213/01.ane.0000278155.19911.67
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Failure to Aspirate Subglottic Secretions with the Evac Endotracheal Tube

Abstract: Evacuation of subglottic secretions using the Evac ETT is often ineffective due to prolapse of tracheal mucosa into the subglottic suction port.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
0
36
0
4
Order By: Relevance
“…A systematic review of 17 eligible trials with 3,369 subjects showed that subglottic secretion drainage tubes helped to reduce VAP rates. 5 However, the reported failure to aspirate subglottic secretions using subglottic secretion drainage had an incidence of 34% in the study by Rello et al 6 and 48% in the study by Dragoumanis et al 7 This high incidence of failure raised safety concerns with subglottic secretion drainage, because the suction port was apparently occluded by suctioned tracheal mucosa, 7 which was the dominant cause of suction lumen dysfunction and a cause of the tracheal membrane injury 8 and laryngeal edema. 9 Other ways have been sought to clear subglottic secretions, such as utilization of high PEEP or plateau pressure generated by a ventilator.…”
Section: See the Related Editorial On Page 1111mentioning
confidence: 99%
“…A systematic review of 17 eligible trials with 3,369 subjects showed that subglottic secretion drainage tubes helped to reduce VAP rates. 5 However, the reported failure to aspirate subglottic secretions using subglottic secretion drainage had an incidence of 34% in the study by Rello et al 6 and 48% in the study by Dragoumanis et al 7 This high incidence of failure raised safety concerns with subglottic secretion drainage, because the suction port was apparently occluded by suctioned tracheal mucosa, 7 which was the dominant cause of suction lumen dysfunction and a cause of the tracheal membrane injury 8 and laryngeal edema. 9 Other ways have been sought to clear subglottic secretions, such as utilization of high PEEP or plateau pressure generated by a ventilator.…”
Section: See the Related Editorial On Page 1111mentioning
confidence: 99%
“…In 17 of the 19 failures, bronchoscopy determined that the subglottic suction lumen was blocked by tracheal mucosa; one subject had a mucus plug, and the other was undetermined due to poor bronchoscopic visibility. 144 Harvey et al 145 reported 2 cases of tracheoesophageal fistula that appeared to be in the vicinity of the SSD suction port. Another study using continuous aspiration of subglottic secretions reported a 40% incidence of postextubation laryngeal edema and considered it an adverse outcome of SSD.…”
Section: Subglottic Secretion Drainagementioning
confidence: 99%
“…The optimal suction pressure is between 20 and 30 mmHg but the clinical variation should be considered, those pressures are sufficient to keep the suction efficient in removing the subglottic secretion specially when there is a viscoid secretion [40], the suction may be continuous or intermittent, it has been proved that both continuous and intermittent has the same effects in the prevention of VAP [35,36], the continuous suction has problems with the mucosa causing herniation of the of the tracheal mucosa into the suction part leading to block of the suction system especially with high suction pressure [41]. While the intermittent suction is better in the mucosal injury, although in the time between the suctions, there may be some leakage between the folds of the cuff and the tracheal causing late onset VAP.…”
Section: Subglottic Secretion Drainage (Ssd)mentioning
confidence: 99%